Assessing the Nutritional Status and Adequacy of Energy and Protein Intakes of Children Admitted to the Pediatric Intensive Care Unit - Dubuc, Alexandra (Université d'Ottawa / University of Ottawa, 2020)
Children admitted to the pediatric intensive care unit (PICU) are at high risk of malnutrition due to the stress of critical illness, and challenges with meeting nutrient needs. The objectives of this study were to describe the prevalence of malnutrition (undernutrition) at admission and discharge from the PICU and the adequacy of dietary intakes during PICU stay according to current practice guidelines. Sixty patients (median age 1.8y) were enrolled. Malnutrition (moderate-severe) was identified in 12% of patients at admission and 15% at discharge using weight-for-length and BMI-for-age z scores. Mid-upper arm circumference z score declined significantly (p=0.002) during PICU stay. Median (IQR) delivery of enteral energy and protein during the first 10 days was 64 (50-73)% and 62 (40-82)%, respectively, of prescribed goal. A total of 174 feeding interruptions were noted in 36 enterally fed patients. Malnutrition was present in the PICU and areas for improvement in nutrient delivery were identified.
Keywords: Nutrition; Critical illness; Pediatric; Nutrition support